VALOR AND VIRTUE: CULTIVATING PATRIOTISM AMONG YOUTH THROUGH THE MILITARY LEGACY OF SULTAN JALALIDDIN MANGUBERDI - Davkarov Akhrorjon Isakovich (Western European Studies, 2024)
This article delves into the relevance of Sultan Jalaliddin Manguberdi's military legacy in shaping the patriotism of today's Uzbek youth. The research emphasizes the necessity of incorporating Manguberdi's narrative into educational curricula and raising awareness through commemorative events. These efforts aim to nurture a sense of national pride and unity among the young generation. Ultimately, the article underscores the power of historical narratives in instilling values of loyalty, sacrifice, and love for the homeland, thereby ensuring the continued strength and unity of the nation
Keywords: Jalaliddin Manguberdi; Mongol invasions; patriotism